Hubungan Kemampuan Literasi Numerasi Sains dengan Hasil Asesmen Kompetensi Minimum (AKM) Numerasi Siswa SMK - Nisa, Rohmi Khoirun; Prihandono, Trapsilo; Supriadi, Bambang (FKIP Universitas Wisnuwardhana, 2024)
The purpose of the study was to analyze the relationship between the science numeracy literacy skills of vocational students and the results of the numeracy AKM assessment. The research method used is descriptive quantitative. The sample of this research is students majoring in Visual Communication Design (DKV) with a sample size of 30 students. Data collection techniques using google forms. The analysis uses the Kolmogorov Smirnov normality test and also the correlation test using the Pearson product moment (r) parametric test if the data is normally distributed and using the Spearman rank non-parametric test. The results of the science numeracy literacy skill question obtained an average value of 43.3, while the numeracy AKM obtained an average value of 58.5. The normality test shows the results of science numeracy literacy ability which is 0.027, then the class AKM shows a value of 0.008. The data shows that the value of science numeracy literacy skills and class AKM scores are not normally distributed. the results of the spearman rank non-parametric correlation test are 0.011 and the correlation level value is 0.456. There is a significant relationship between science numeracy literacy skills and numeracy AKM scores and has a moderate degree of relationship.